Major impact investor group mobilizes USD 106 million for a climate-smart food systems strategy designed with Alliance-led CCAFS technical guidance. - Wollenberg, Eva (2024)
The Alliance provided science-based metrics for designing the Sustainable Food Systems impact investment fund at responsAbility, a major global impact investor. The Fund’s success depends on securing funding. In 2023, the Fund secured USD 106 million from public and private sector impact investors. Kreditanstalt für Wiederaufbau (KfW) served as the anchor investor, while the U.S. International Development Finance Corporation (DFC) functioned as the Fund guarantor.